The role of intermolecular forces in contact electrification on polymer surfaces and triboelectric nanogenerators - Šutka, Andris; Mālnieks, Kaspars; Lapcinskis, Linards; Kaufelde, Paula; Linarts, Artis; Bērziņa, Astrīda; Zābels, Roberts; Jurkāns, Vilnis; Gornēvs, Ilgvars; Blums, Juris; Knite, Māris (Royal Society of Chemistry, 2019)
The contact electrification of polymer interfaces provides an energy harvesting function to triboelectric (nano)generators (TEG). The electron transfer between contacted-separated surfaces has been considered as the main electrification mechanism for polymers in TEG. The electron transfer mechanism widely proposed in literature requires a contact between chemically different polymer materials, as well as subsequent increase of the specific contact area, which is commonly accomplished via nanostructuring. Herein, we showed that contact electrification could be controlled by intramolecular forces in the polymer bulk and adhesive forces at the contact interface, and the chemical contact between different polymers was not needed for contact electrification. The results also confirm the breaking of the covalent bond as a mechanism of the contact electrification of polymer insulators.
This research was supported by the European Regional Development Fund within the project ‘‘Hybrid energy harvesting systems’’ 1.1.1.1./16/A/013.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics